2013
DOI: 10.1038/nm.3111
|View full text |Cite
|
Sign up to set email alerts
|

Peli1 promotes microglia-mediated CNS inflammation by regulating Traf3 degradation

Abstract: Microglia are crucial for the pathogenesis of multiple sclerosis and its animal model, experimental autoimmune encephalomyelitis (EAE). Here, we show that the E3 ubiquitin ligase Peli1 is abundantly expressed in microglia and serves as a pivotal mediator of microglial activation during the course of EAE induction. Peli1 mediates the induction of chemokines and proinflammatory cytokines in microglia and, thereby, promotes recruitment of T cells into the central nervous system. Peli1-deficient mice are refractor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
235
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(246 citation statements)
references
References 43 publications
11
235
0
Order By: Relevance
“…In addition to this newly identified function of TRAF3 in bone homeostasis, TRAF3 has been implicated in the pathogenesis of a number of diseases, including multiple myeloma (63) and experimental autoimmune encephalomyelitis/multiple sclerosis (64). TRAF3 mutations in humans with multiple myeloma result in the accumulation of NIK and constitutive activation of NF-κB, thereby promoting myeloma cell survival.…”
Section: Relb Is Required For Rankl-induced Traf3 Lysosomal Degradatimentioning
confidence: 99%
“…In addition to this newly identified function of TRAF3 in bone homeostasis, TRAF3 has been implicated in the pathogenesis of a number of diseases, including multiple myeloma (63) and experimental autoimmune encephalomyelitis/multiple sclerosis (64). TRAF3 mutations in humans with multiple myeloma result in the accumulation of NIK and constitutive activation of NF-κB, thereby promoting myeloma cell survival.…”
Section: Relb Is Required For Rankl-induced Traf3 Lysosomal Degradatimentioning
confidence: 99%
“…Peli1 activates inhibitor of apoptosis‐2, which in turn facilitates the degradation of tumor necrosis factor receptor–associated factor‐3 and liberates MK2 to activate NFκB 33. Accordingly, a deficiency of Peli1 in microglial cells has been shown to be associated with reduced activation of IAP2 and MK2 14. In this study we established that Peli1 could also upregulate MK2 activation in heart tissue to stimulate angiogenesis.…”
Section: Discussionmentioning
confidence: 56%
“…Although the immunological effects of Peli1 have been extensively studied, the involvement of Peli1 in angiogenesis has not yet been examined. Peli1 upregulates MK2 through ubiquitination and activation of inhibitor of apoptosis‐2 (IAP2), which in turn facilitates the ubiquitination and degradation of tumor necrosis factor receptor–associated factor‐3, a negative regulator of MK2 14. Peli1 also plays a role in the activation of NFκB 13.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that TRAF3 expression was crucial for the Peli1-induced microglia activation in an experimental model of multiple sclerosis (17). Peli1 is an E3 ubiquitin ligase highly expressed in microglia, which regulates microglia activation through the regulation of a signalling pathway which leads to TRAF3 degradation (Table 1) (17).…”
Section: Traf3 and Neurological Diseasesmentioning
confidence: 99%
“…TRAF3 is necessary for sustained B cells activation mediated by LMP1 through the downstream activation of JNK and NF-κβ (Table 1) (14). (13,15,16) NF-κβ, JNK and Rac-1 Stroke, SCI B cell activation (14) NF-κβ and JNK Multiple myeloma, EBV infection Microglia activation (17) MAPK and NF-κβ Multiple sclerosis Osteoclastogenesis (21) NF-κβ Osteoporosis Platelet aggregation (23) Vascular recurrence in patients treated with clopidogrel HIV, human immunodeficiency virus; SCI, spinal cord injury; EBV, Epstein-Barr virus. In addition, CD40, a TNF receptor, and LMP1 share TRAF3 for signal transduction in the activation of B cells (14).…”
Section: Introductionmentioning
confidence: 99%